Examination milling non-uniformity in friction rice mills using by discrete element method and experiment. (November 2021) - Li, Anqi; Han, Yanlong; Jia, Fuguo; Zhang, Jincheng; Meng, Xiangyi; Chen, Peiyu; Xiao, Yawen; Zhao, Hongwei
Abstract : The uniformity of rice milling is of vital significance in the rice processing industry. Unfortunately, the reasons for non-uniform milling of grains in friction rice mills still remain poorly understood. In this paper, the motion of rice in the mill is numerically simulated based on the discrete element method. The removal mechanism for the bran layer in the friction mill is discussed and verified by experiment. A method of quantifying milling uniformity was introduced. The results showed that for successful milling, the intact bran layer must experience abrasion caused by sieve-rice contact then be completely removed by rice–rice friction. Non-uniform milling occurs due to the existence of "milling blind zones", where the bran layer cannot be removed. Milling uniformity is closely related to the ability of rice to move from blind zones to the outer ring of the mill. The use of alternating rate to quantify this ability is proposed. The higher alternating rate the better milling uniformity. Alternation rate is affected by the tumbling movement of rice in the milling cavity. The research helps clarify the milling process of rice and provides guidance for the design of rice friction mills. Graphical abstract: Image 1 Highlights: Removal of bran layer mainly depends on the abrasion effect by sieve. Non-uniform milling is due to existence of milling blind zones. Higher alternating rate between zones is beneficial for milling uniformity. Stronger tumbling ability of rice grains can lead to higher alternating rates.